COPING WITH EXAMS: DEVELOPMENTS OF MAYOR THEORETICAL MODELS FOR ITS DEFINITION AND MEASUREMENT. - Piemontesi, Sebastián Eduardo; Heredia, Daniel Esteban (Anales de Psicología / Annals of Psychology, 2009)
The transactional model of coping developed by Lazarus and Folkman (1984) has been the most accepted model in research on coping. Its contributions have enabled the study of exams as a specific stress situation characterized as a complex process with significant changes in the use of various strategies through different stages. Although, there are numerous studies and coping measures created from this model, their developments have been complemented by the contributions of the multi-axial and proactive coping model, which highlights the capacity of social networks to identify coping behaviors as well as the ability to anticipate stressful situations by cognitive and behavioral processes to find the best strategies, respectively. All these models have developed instruments for measuring both general and specific to exams situations, some of which are described in this article.